Isolation and Characterisation of Salmonella spp. from Water in Aquaculture Farms - Scholastica Ramih, Bunya (Universiti Malaysia Sarawak (UNIMAS), 2018)
Aquaculture has become one of the world largest industries due to high demand of aquaculture products as a part of food supply. In Malaysia, aquaculture especially in freshwater pond aquaculture has developed quickly and become an important activity. In spite of that, chloramphenicol, one of the banned antibiotics in aquaculture, is illegal used of this antibiotic become a major concern due to the safety of consumer which depends on the development of drug resistant strains in bacterial Salmonella spp. Due to the circumstances stated above, the objectives of this study were to isolate the Salmonella spp. from water in both traditional and commercial farm, to detect the chloramphenicol resistance gene in Salmonella spp. isolated from both traditional and commercial farm and to determine the susceptibility of Salmonella spp. towards chloramphenicol by using antibiotic susceptibility test. Salmonella spp. that isolated from aquaculture farms were grown selectively on XLD agar and assessed for antibiotic susceptibility test using chloramphenicol disks. The corresponding chloramphenicol resistance genes in the isolates were detected by specific PCR which targeted the catP gene. The chloramphenicol susceptibility test showed that 15 (79%) isolates were susceptible towards chloramphenicol, while 4 (21 %) isolates were intermediate resistance to chloramphenicol. Based on this study, 17 out of 20 isolates including the Salmonella spp. control were detected with catP gene. These findings provided information on chloramphenicol resistance profiles of Salmonella spp. in aquaculture farms to control the usage of antibiotics in aquaculture